Illustration of Capacity Fading Factors on the Example of La2(Li0.5Ni0.5)O4‐Modified High Nickel Layered Oxide Material. Issue 3 (18th January 2023) - Ivanishcheva, Irina A.; Ivanishchev, Aleksandr V.; Chang, Joon Ha; Song, Jung‐Hoon; Lee, Su‐Hyun; Kim, Jae‐Joong; Kim, Young Je; Nam, Sang‐Cheol
Abstract: Modifying of layered oxide NCM (LiNi0.85 Co0.1 Mn0.05 O2 ) with high nickel (Ni) content is a popular strategy for development of energy‐dense cathode materials for LIBs. In spite of long‐time investigations of their electrochemical performance there is no clear understanding of the predominant capacity fading reasons as well as the mechanism of suppression of performance degradation for modified samples. In the present work, NCM (bare and washed) powders were modified by perovskite‐like phase La2 (Li0.5 Ni0.5 )O4 (LNP), using lithium residual compounds (LRC) from NCM surface. Initial properties of NCM‐materials were under our focus in terms of structural data of pristine powders and the first cycle capacity loss. We observed that incomplete lithium extraction in case of LNP‐modified NCM bare sample preserves electrochemical performance. For illustration of the main reasons of capacity fading new type Δ ‐plots were proposed. Based on their analysis we highlighted two factors, affecting on capacity retention. Our conclusions were supported by D vs. E dependence analysis from GITT measurements. Abstract : (Ir)reversible capacity fading : New type of plots illustrate the influence of two kinds of degradation factors on the capacity retention of NCM cathode material with high Ni content. La2 (Li0.5 Ni0.5 )O4 ‐surface modification of bare powder suppresses irreversible capacity loss and improves its cycle life.